2016
DOI: 10.1111/add.13291
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of drinking urges and the initiation of abstinence during cognitive–behavioral alcohol treatment

Abstract: Background and aims Drinking urges during treatment for alcohol use disorders (AUDs) are common, can cause distress, and predict relapse. Clients may have little awareness of how their drinking urges might be expected to change during AUD treatment in general and in response to initiating abstinence. The aim of the present study was to test whether drinking urges change on a daily level during treatment and after initiating abstinence. Design Secondary data analysis was performed using daily drinking urge ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The present study aims to replicate this previous study that found reductions in daily craving associated with initiating abstinence (Hallgren et al, 2016) under improved methodological conditions, including the use of interactive voice response (IVR) technology to ensure same-day data collection (versus hand-written daily diaries asking patients to report on urges when they occur) and the use of multiple items that assessed different facets of daily craving including frequency and intensity (versus a single item assessing the presence or absence of any daily cravings). The present study also extends this previous work by evaluating changes in daily negative affect (versus only craving) and by studying these changes in the context of a pharmacotherapy trial with no behavioral intervention (versus cognitive-behavioral treatments that include substantial education and psychotherapy around craving and negative affect).…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…The present study aims to replicate this previous study that found reductions in daily craving associated with initiating abstinence (Hallgren et al, 2016) under improved methodological conditions, including the use of interactive voice response (IVR) technology to ensure same-day data collection (versus hand-written daily diaries asking patients to report on urges when they occur) and the use of multiple items that assessed different facets of daily craving including frequency and intensity (versus a single item assessing the presence or absence of any daily cravings). The present study also extends this previous work by evaluating changes in daily negative affect (versus only craving) and by studying these changes in the context of a pharmacotherapy trial with no behavioral intervention (versus cognitive-behavioral treatments that include substantial education and psychotherapy around craving and negative affect).…”
Section: Introductionmentioning
confidence: 53%
“…Among 92 participants in the parent study, a total of N =78 had enough daily IVR drinking data to assess an abstinence status over 14 or more consecutive days. Following identical procedures to Hallgren et al (2016), these 78 participants were classified into three groups based on whether and when they first initiated 14 consecutive days of abstinence from alcohol during treatment. Abstinence initiators ( n =17) drank on at least one of the first 14 days of treatment then eventually obtained at least 14 consecutive days of abstinence during the treatment period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Hallgren and colleagues had found that daily-rated alcohol craving (a different mediator) decreased in relation to initiation of abstinence in men and women in outpatient CBT for AUD. 91 …”
Section: Aud Treatment Services For Womenmentioning
confidence: 99%